The Role of International Standards on Auditing in Improving the Performance of the Financial Audit Profession in Algeria: A Survey of a Sample of Academics and Professionals in The Field of Financial Auditing - Amar, Dilmi; lakhdar, Loglaithi (The Arab Journal of Administration, 2020)
In order to improve and develop the performance of financial audit profession in Algeria, academics and professionals in the field of financial audit see that international auditing standards are considered as an important reference that may be relied upon, as the application of international standards enables audit firms in Algeria to review national and foreign institutions accounts and to compete with international firms. As well as to support the independence of auditors, and to reduce the risks relating to the expression of opinion. In addition, to activate the professional performance quality control program of the auditors, and the mechanisms of bodies that regulate the profession. The application of international standards helps Algeria join the International organizations of audit, and international financial and economic organizations; such as the World Trade Organization. The performance of the auditing profession in Algeria can be improved through enhancing the auditors’ academic qualifications by teaching international curricula at the Algerian universities and institutions of auditors, especially concerning the application of the international auditing standards. In addition to developing scholarships polices for financial auditors’ studying abroad, and reconsideration the licensing and organizing audit firms. Furthermore, building relationships with international audit firms, which are based on the international auditing standards, with the aim of sharing the countries’ successful experiments in the enhancement and the development of auditing profession.